Modelling learning environment for digitization in secondary schools in Ibadan metropolis Nigeria (2018)
In Nigeria, a common unspoken beliefs that secondary schools are not technically matured to accommodate high level innovations in digitalization and modeling hence this study investigated digital readiness of secondary school environments in an in-depth study of Ibadan Metropolis as it has permeated other professions. The descriptive survey research type with total population of secondary schools in Ibadan Metropolis that sampled 483 teachers was adopted. The research instrument used for the study was validated with a Cronbach alpha reliability r=0.74. The result of the study indicated that level of ICT ubiquity had no significant relationship with level of digitalization (r=0.096, p>0.05). However, affordability (r=0.340, p<0.05), Usability (r=0.191, p<0.05), reliability (r=0.249, p<0.05), speed of using ICT (r=0.118, p<0.05) and secondary schools stakeholders’ ICT skills (r=0.432, p<0.05) significantly correlated with level of digitalization in the secondary schools. Fit indexes of validated model revealed; Normed fit index (NFI) = 0.00> 0.95; Comparative fit index (CFI) = 0.99>0.90; Root mean square error of approximation (RMSEA) = 0.000<.06. The reduced model gained an incremental fitness over the hypothesized ones x2(8) = 12.621, p>.0.05. The proportion of direct to indirect effect of indicators in the model reveal that 89.0% of the relationship between digitization indicators and level of digitalization are direct while 11.0% are indirect. The study concluded that secondary schools learning environment could accommodate digitalization, facilities for modeling and digitalization should be provided for schools.